Outcomes of pancreatic cancer with liver oligometastasis. (1st June 2022) - Takeda, Tsuyoshi; Sasaki, Takashi; Okamoto, Takeshi; Kasuga, Akiyoshi; Matsuyama, Masato; Ozaka, Masato; Inoue, Yosuke; Takahashi, Yu; Saiura, Akio; Sasahira, Naoki
Abstract: Background: Liver oligometastatic pancreatic cancer (PC) may have favorable outcomes. This study aims to evaluate outcomes and factors associated with overall survival (OS) of these patients. Methods: We retrospectively investigated consecutive PC patients with liver metastasis treated at our institution between 2013 and 2020. Clinical characteristics and outcomes were compared and analyzed according to the extent of liver metastasis. Cox proportional hazards model was used to identify prognostic factors for OS. Results: A total of 417 patients were included (multi‐organ metastasis/polymetastasis/oligometastasis 174/158/85). Oligometastasis showed a longer OS compared to other types of metastases (7.7 vs 8.2 vs 13.1 months). Age <70 years, performance status of 0, modified Glasgow prognostic score of 0, carbohydrate antigen 19‐9 <1000 U/mL were identified as significant prognostic factors for OS. A prognostic index consisting of these four factors successfully stratified the prognosis of these patients (prognostic index; high vs low, 19.9 vs 8.3 months). Highly selected patients who underwent surgical resection showed a median OS of 54.6 months. Conclusions: Oligometastasis presented a relatively favorable outcome. Our new prognostic index was useful in stratifying the prognosis of these patients. Multimodal treatment including surgery may have additional survival benefits for highly selected patients. Abstract : Takeda and colleagues evaluated outcomes and factors associated with survival of patients with liver oligometastatic pancreatic cancer. Their new prognostic index was useful for stratifying the prognosis of these patients. Objective response to chemotherapy was most important for long‐term survival. Conversion surgery may have additional benefit for highly selected patients.